Exercise dependence - Kerr, J. H.; Lindner, K. J.; Blaydon, M. (Routledge, 2007)
Exercise dependence or addiction has been described as a positive addiction, but it can have links with damaging dysfunctional and excessive behaviours, including eating disorders. Clinical and sport psychologists now acknowledge the condition and report that it can be found in recreational exercisers and competitive athletes.